In-situ formation of nitrogen doped microporous carbon nanospheres derived from polystyrene as lubricant additives for anti-wear and friction reduction - Yixin Wang; Qi Lu; Huijie Xie; Shujuan Liu; Qian Ye; Feng Zhou; Weimin Liu (Friction)
Abstract This study presents a nitrogen-doped microporous carbon nanospheres (N@MCNs) prepared by a facile polymerization–carbonization process using low-cost styrene. The N element in situ introduces polystyrene (PS) nanospheres via emulsion polymerization of styrene with cyanuric chloride as crosslinking agent, and then carbonization obtains N@MCNs. The as-prepared carbon nanospheres possess the complete spherical structure and adjustable nitrogen amount by controlling the relative proportion of tetrachloromethane and cyanuric chloride. The friction performance of N@MCNs as lubricating oil additives was surveyed utilizing the friction experiment of ball-disc structure. The results showed that N@MCNs exhibit superb reduction performance of friction and wear. When the addition of N@MCNs was 0.06 wt%, the friction coefficient of PAO-10 decreased from 0.188 to 0.105, and the wear volume reduced by 94.4%. The width and depth of wear marks of N@MCNs decreased by 49.2% and 94.5%, respectively. The carrying capacity of load was rocketed from 100 to 400 N concurrently. Through the analysis of the lubrication mechanism, the result manifested that the prepared N@MCNs enter clearance of the friction pair, transform the sliding friction into the mixed friction of sliding and rolling, and repair the contact surface through the repair effect. Furthermore, the tribochemical reaction between nanoparticles and friction pairs forms a protective film containing nitride and metal oxides, which can avert direct contact with the matrix and improve the tribological properties. This experiment showed that nitrogen-doped polystyrene-based carbon nanospheres prepared by in-situ doping are the promising materials for wear resistance and reducing friction. This preparing method can be ulteriorly expanded to multi-element co-permeable materials. Nitrogen and boron co-doped carbon nanospheres (B,N@MCNs) were prepared by mixed carbonization of N-enriched PS and boric acid, and exhibited high load carrying capacity and good tribological properties.